Penggunaan Instagram sebagai Strategi dalam Menarik Minat Wisatawan saat Pandemi COVID-19 di Jakarta Aquarium, Indonesia - Putri, Kezia Tanri; Sanjiwani, Putri Kusuma (JURNAL DESTINASI PARIWISATA, 2022)
The COVID-19 pandemic is a major blow to the tourism industry. Creative and relevant ideas should be implemented to support the tourism sector. Due to the shift in technological developments, promoting businesses using this technology is often found. Instagram has been one of the choices to promote a tourist attraction. In Jakarta, there are a lot of tourist attractions that used Instagram as a media to promote their attractions. One of them is Jakarta Aquarium. Jakarta Aquarium is the largest indoor aquarium tourist attraction at Neo Soho Mall, West Jakarta. This research aims to see the effectiveness of Instagram as social media in promoting tourism attractions. This research used a mixed method, using both qualitative and quantitative approaches. The data were collected through observation, literature study, documentation, and online questionnaires. The theory used in this study is the Tourist Motivation in Traveling. The research results showed, tourists’ visit Jakarta Aquarium were strongly influenced by the promotion of social media Instagram. Keywords: Promotion, Instagram, COVID-19, Tourist Motivation, Jakarta Aquarium